Makna Dan Fungsi Itikad Baik Dalam Kontrak Kerja Konstruksi - Barnabas Dumas Manery (Faculty of Law, Universitas Pattimura, 2017)
Neither law nor doctrine can provide a clear understanding of good faith in contract law. In general, the study of good faith tends to mix up the notion of good faith as the rule of law in good faith as the principle of contract law. Based on this understanding, Article 1338 Paragraph (3) BW is considered as the legal principle of the contract so it concludes that the obligation of good faith exists only at the stage of contract implementation. Such opinion has obscured the meaning and function of good faith as the principle of contract law, which became the legal issue in this study. The approach used is (statute approach), (case approach), and (conceptual approach). Based on the results of the research, it is found that the essence of good faith is honesty and fairness which contains the meaning of trust, transparency, autonomy, obedience, without coercion and without deceit; as well as the function of the principle of good faith is to complement the legal system through the legislator and authorize through the authority of the judge in the form of adding, limiting and excluding a contractual obligation. Thus the law becomes flexible and able to guarantee complex and dynamic community legal needs.